2012
DOI: 10.1002/cphc.201100721
|View full text |Cite
|
Sign up to set email alerts
|

Solute‐Induced Microstructural Transition from Weak Aggregates towards a Curved Film of Surface‐Active Extractants

Abstract: Reverse micelles? The transition from weak aggregation to water‐poor reverse micelles triggered by the presence of extracted ion pairs is modeled using molecular dynamics simulations (see picture). The presence of the ion induces a polar/apolar segregation and the formation of a curved film microstructure consistent with the classical inverse micelle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
25
1
Order By: Relevance
“…These aggregates are not always formed around a cluster of water molecules (Figure 2: red and light-gray), but can be considered as rather compact and stable when they exist. [19] However, the ideal picture of a polar core surrounded by aliphatic chains and the solvent, as considered in classical SAXS analysis, does not appear in this simulation. The Fourier transform of the radial distribution functions presents a similar shape of the structure factor, characterized by an intense peak around 14.2 nm À1 and an upturn with a leveling off at lower q-vectors, as observed in the experimental data (Figure 1, bottom).…”
Section: Methodsmentioning
confidence: 91%
“…These aggregates are not always formed around a cluster of water molecules (Figure 2: red and light-gray), but can be considered as rather compact and stable when they exist. [19] However, the ideal picture of a polar core surrounded by aliphatic chains and the solvent, as considered in classical SAXS analysis, does not appear in this simulation. The Fourier transform of the radial distribution functions presents a similar shape of the structure factor, characterized by an intense peak around 14.2 nm À1 and an upturn with a leveling off at lower q-vectors, as observed in the experimental data (Figure 1, bottom).…”
Section: Methodsmentioning
confidence: 91%
“…[58] Moreover, the reverse aggregates exist in organized and more diffuse forms, with a noticeable difference in free energy of formation of the aggregates. [59] CONCLUSIONS This article shows that the acid extraction by an extractant molecule like DMDOHEMA can be described with a Langmuir like isotherm adsorption model, taking into account the aggregation of the ligands and considering that the acids are adsorbed at the interface dispersed in the form of reverse aggregates in the organic phase. In this approach, the solute is extracted in the organic phase by a host surface which is offered by the sum of all the extractant polar heads gathered in the aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Closer examinations of extractant aggregate formation in pure nheptane have shown that the amount of water molecules, and/or cation salts has a significant influence on these aggregate shapes [27]. Solvent extraction experiments involve an interfacial transfer of a coordinating metal ion from an aqueous solution into a water-poor microemulsion [25].…”
Section: Reverse Micelles and Reverse Aggregates: The Role Of Nucleationmentioning
confidence: 99%